“HOW DO THE BROCHURES SPEAK?” SYSTEMIC FUNCTIONAL LINGUISTICS ANALYSIS IN ONLINE PARENTING BROCHURES - Syafitri, Siska Eka; Sinar, Tengku Silvana; Mulyadi, Mulyadi; Lubis, Masdiana (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Online brochures are one of the preferred choices in describing the advertisement’s worth of many linguistic features. ‘Parenting’ strategies are one of the topics which are discussed in the online brochures. We can find the quotes and problem-solving about ‘parenting’ spread in cyberspace. Online parenting brochures are made by a personal or community to share that importance. The clause in parenting brochures discourse has a semantic meaning of its speech function. The language of the brochures was examined by using Halliday’s theory of Systemic Functional Linguistics (SFL), then it was found that the language in the brochures was formulated interpersonally. The meanings of the clause are developed in any interactive features in exchanging the giving and demanding move of speech function. This research was conducted qualitatively by analyzing 48 clauses in the brochures. It was found that the most commonly used linguistic clause in the brochures was the statement (71%) as a way of giving information to the readers. Then the rest was the command (29%) for the parents or the childminder to be applied in nurturing the children. Besides, multimodal strategies were also used to make the brochures more eye-catching. The semiotics modes used in the brochures were supported by the meaning making of the discourse. The readers were also invited to comprehend the urgent situation of the topic discussed.